Venture capital exit rights - Carsten Bienz; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Theorists argue that exit rights can mitigate hold-up problems in venture capital. Using a hand-collected data-set of venture capital contracts from Germany we show that exit rights are included more frequently in venture capital contracts when a hold-up problem associated with the venture capitalist's exit decision is likely. Examples include drag-along and tag-along rights. Additionally, we find that almost all exit rights are allocated to the venture capitalist rather than to the entrepreneur. In addition, we show that besides the basic hold-up mechanism there are other mechanisms such as ex-ante bargaining power and the degree of pledgeable income that drive the allocation of exit rights.
urn:nbn:de:hebis:30-63764
Keywords: G24; G34; D80; 330; Venture Capital; Corporate Governance; Empirical Contract Theory; Hold-up; Exit Rights; Trade-sale Rights; Risikokapital; Liquidation; Vertrag; Sunk Costs; Corporate Governance; Deutschland